Retrograded garnet peridotites from Col des Bagenelles and Crébimont in the Variscan Vosges Mountains (NE France) - Altherr, Rainer (Contributions to mineralogy and petrology, 2021)
Like the Moldanubian parts of the Bohemian Massif and the French Massif Central, the Vosges Mts (NE France) comprise an uppermost tectonic unit that consists of retrograded (U)HP/UHT granulites, eclogites and garnet peridotites, originally metamorphosed at pressures of ≥ 4 GPa and temperatures of ≥ 950 °C. Two amphibole-garnet-spinel-bearing peridotite bodies located near to Col des Bagenelles (CB) and Crébimont (CR) show a pronounced retrograde evolution. Primary garnet was completely transformed to a symplectite of orthopyroxene + clinopyroxene + Cr-poor spinel ± amphibole, partially surrounded by a discontinuous outer zone of coarser grains of pyroxenes ± amphibole. Such symplectites are typical for the sliding reaction garnet + olivine ± Na2O ± K2O ± H2O = orthopyroxene + clinopyroxene + spinel ± amphibole. Both peridotites contain ‘primary’ Cr-Al-spinel. In the sample from CB, such grains occur only within the symplectites after garnet, but never in the matrix, while in the sample from CR, Cr-Al-spinel is present as inclusions within the symplectites and as isolated grains within the surrounding matrix. In the peridotite from CR, that is more depleted than that from CB, these Cr-Al-spinel grains show intense chemical zoning with Cr and Fe2+ decreasing, but Al and Mg increasing from core to rim. This pattern is interpreted as retrograde zoning during decompression. Primary P-T conditions deduced from compositions of matrix pyroxenes under the assumption of equilibration with earlier garnet are ≥ 1.6-1.7 GPa/ ≥ 900 °C for sample CB, but ≥ 2.3 GPa/ ≥ 860 °C for sample CR. Temperature conditions during the breakdown of garnet are indicated by pyroxenes from the symplectites and are 833 ± 18 (CB) and 812 ± 11 °C (CR) using the Ca-in-Opx thermometer at a chosen pressure of 1.3 GPa.